PENGARUH PENGGUNAAN METODE PENEMUAN (DISCOVERY LEARNING) TERHADAP HASIL BELAJAR SISWA - Ria Eka Susianti (Universitas Muhammadiyah Lampung, 2022)
A planned effort to develop one's potential and change one's attitude and way of thinking to interact in daily life so that how to behave for the better is the meaning of education. Mastery of concepts is very much needed in the learning process in the classroom but in fact there are still many students who do not understand the concept so that learning outcomes are still low, one of the causes of the lack of mastery of learning concepts in class is the lack of variety in learning or the use of classical learning methods makes students bored and bored to follow the learning process in class so that the material presented by the teacher is not conveyed properly to students. The method used in this study using descriptive quantitative methods, the data were analyzed using statistical calculations for the population in this study were all students of class VII SMP SLB Lampung Province which consisted of 2 classes with a total of 16 students, while the sample was taken 2 classes, namely class VII.A and class VII.B. To find out student results, an essay test was conducted. From the results of testing the hypothesis using the statistical formula t-test obtained the value of t = 3.08. From the t distribution table at the 5% significant level, it is known that t = 2.14 and t = 1.76, while at the 1% significant level it is known that t = t= 2.98 and t = 2.62, this means t > t